ANALISIS KOORDINASI OLEH KEPALA DINAS DALAM RANGKA PENINGKATAN EFEKTIVITAS KERJA PEGAWAI DI DINAS PEMUDA OLAHRAGA KEBUDAYAAN DAN PARIWISATA KOTA CIREBON - Lias Nurlantina; I Machmud; Sri Wulandari (Jurnal Ilmiah Publika, 2015)
ABSTRACT The title of this research is "Analysis of Coordination by the Head in the Framework of Improving the Effectiveness of Workers' Effectiveness in the Cirebon City Sports and Culture Youth Office".The problem that the authors put forward from the observations that the authors found at the time of the research is that the implementation of employee work is less than optimal in order to achieve the objectives seen from the quality of employee work that is not as expected in achieving the goals, it is seen from the state of facilities and infrastructure in the Sports Culture Youth Service and Cirebon City Tourism is inadequate in terms of the number of employees and each field that is not in accordance with the expertise so that the quantity of employee work is less visible than the less optimal implementation of employee work activities in order to improve performance in the city of Cirebon. The lack of understanding of employees and lack of coordination between leaders and employees is not optimal where it is in accordance with the opinion of Stoner (in Sugandha 2005: 21) argues as follows: "Coordination is the process of integrating targets and activities of units that separate (parts and functional fields) of an organization to achieve organizational goals efficiently".Identification of problems in the research is how coordination is done by the Head of Service in order to improve employee work effectiveness, coordinating support factors by the service head in order to improve employee work effectiveness, and factors inhibiting coordination by the service head in order to improve employee work effectiveness in the Office Cirebon Sports Culture and Tourism Youth.The method used by the author is a qualitative method through a descriptive approach. According to Moleong (2007: 6) suggests qualitative research as follows: "Qualitative research is research intended to understand the phenomenon of what is experienced by research subjects, such as behavior, perception, motivation, actions, and others. Holistically and by way of description in the form of words and languages. In a special natural context and by utilizing various scientific methods.